Gene-Environment Complementarity in Educational Attainment - Muslimova, Dilnoza; van Kippersluis, Hans; Rietveld, Cornelius A.; von Hinke, Stephanie; Meddens, S. Fleur W. (Journal of Labor Economics, 2026)
Firstborns, on average, complete more education than laterborns. We study whether individuals’ endowments measured by genetic information amplify this effect. Our familyfixed effects approach allows exploiting exogenous variation in birth order and genetic endowments among 14,850 siblings in the UK Biobank. We find that those with higher genetic endowments benefit disproportionately more from being firstborn compared to those with lower endowments, providing a clean example of how nature and nurture interact in producing human capital. Since parental investments are a dominant channel driving birth order effects, our results are consistent with complementarity between endowments and investments in human capital formation.